2012
DOI: 10.2967/jnumed.112.103127
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Hybrid Fluorescent–Radioactive Tracer Indocyanine Green–99mTc-Nanocolloid with 99mTc-Nanocolloid for Sentinel Node Identification: A Validation Study Using Lymphoscintigraphy and SPECT/CT

Abstract: The purpose of this study was to compare the lymphoscintigraphic drainage patterns of a hybrid sentinel node tracer consisting of the fluorescent dye indocyanine green (ICG) and 99m Tc-nanocolloid with the drainage pattern of 99m Tc-nanocolloid alone, the current standard tracer in many European countries. Methods: Twenty-five patients with a melanoma in the head and neck region (n 5 10), a melanoma on the trunk (n 5 6), or penile carcinoma (n 5 9) who were scheduled for sentinel node biopsy were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(124 citation statements)
references
References 29 publications
4
113
0
1
Order By: Relevance
“…Nontargeted dually labeled tracers were applied for sentinel lymph node biopsy and resection after intratumoral injection of nanocolloid in a clinical setting (20). The results clearly demonstrated improved lymph node detection, especially when positive nodes were located in lymph node-rich regions, as in prostate cancer or head and neck cancer (21,22). A study with patients who had ovarian cancer had already shown the feasibility and potential of this approach for intraoperative fluorescence imaging in a clinical setting (23).…”
Section: Discussionmentioning
confidence: 99%
“…Nontargeted dually labeled tracers were applied for sentinel lymph node biopsy and resection after intratumoral injection of nanocolloid in a clinical setting (20). The results clearly demonstrated improved lymph node detection, especially when positive nodes were located in lymph node-rich regions, as in prostate cancer or head and neck cancer (21,22). A study with patients who had ovarian cancer had already shown the feasibility and potential of this approach for intraoperative fluorescence imaging in a clinical setting (23).…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc-tilmanocept has the ability to migrate quickly through the afferent lymph vessels because of its small size, as well as the ability to reside within sentinel lymph nodes because of its specific binding. A hybrid fluorescent radioactive tracer has also been applied for sentinel node identification by mixing indocyanine green with 99m Tc-labeled albumin nanocolloid (62).…”
Section: Nanocolloidalmentioning
confidence: 99%
“…Such shortcomings can be overcome using a hybrid tracer, for example, ICG-99m Tcnanocolloid, a tracer that contains both a radioisotope and an optical fluorescent dye. The clinical value of ICG-99m Tc-nanocolloid has already been extensively demonstrated by us (12)(13)(14) and others (11,15) whereby it was shown that using the hybrid tracer allows for direct translation of (in-depth) preoperative imaging findings into the operation theater. The radiolabel of the hybrid tracer allows preoperative SN mapping in a fashion similar to the conventional radioguided approach (12), meaning it also provides directional information for the placement of the incisions.…”
mentioning
confidence: 99%
“…The clinical value of ICG-99m Tc-nanocolloid has already been extensively demonstrated by us (12)(13)(14) and others (11,15) whereby it was shown that using the hybrid tracer allows for direct translation of (in-depth) preoperative imaging findings into the operation theater. The radiolabel of the hybrid tracer allows preoperative SN mapping in a fashion similar to the conventional radioguided approach (12), meaning it also provides directional information for the placement of the incisions. During the operation, the combination of radio-and fluorescence guidance can be used to refine this even further by confirming the actual location and removal of the SNs defined at preoperative imaging (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation